2021
DOI: 10.1186/s12951-021-01026-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanoceria seed priming enhanced salt tolerance in rapeseed through modulating ROS homeostasis and α-amylase activities

Abstract: Background Salinity is a big threat to agriculture by limiting crop production. Nanopriming (seed priming with nanomaterials) is an emerged approach to improve plant stress tolerance; however, our knowledge about the underlying mechanisms is limited. Results Herein, we used cerium oxide nanoparticles (nanoceria) to prime rapeseeds and investigated the possible mechanisms behind nanoceria improved rapeseed salt tolerance. We synthesized and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 97 publications
(132 reference statements)
10
38
0
Order By: Relevance
“…For example, nanozyme poly(acrylic) acid-coated cerium oxide nanoparticles (PNC) can improve salinity stress tolerance of cotton mainly by alleviating ROS accumulation in seedling roots ( An et al, 2020 ). Similar results were also found in wheat ( Mushtaq et al, 2017 ), tomato ( Faizan et al, 2021 ), soybean ( Farhangi-Abriz and Torabian, 2018 ), and rapeseed ( Khan et al, 2021 ). Carbon quantum dots can significantly improve the activity of antioxidant enzyme system to reduce the content of ROS and to alleviate oxidative damage on cell membrane, thus enhancing grape salt tolerance ( Gohari et al, 2021 ).…”
Section: Plant’s Ability To Alleviate Oxidative Stress Is Important F...supporting
confidence: 77%
See 2 more Smart Citations
“…For example, nanozyme poly(acrylic) acid-coated cerium oxide nanoparticles (PNC) can improve salinity stress tolerance of cotton mainly by alleviating ROS accumulation in seedling roots ( An et al, 2020 ). Similar results were also found in wheat ( Mushtaq et al, 2017 ), tomato ( Faizan et al, 2021 ), soybean ( Farhangi-Abriz and Torabian, 2018 ), and rapeseed ( Khan et al, 2021 ). Carbon quantum dots can significantly improve the activity of antioxidant enzyme system to reduce the content of ROS and to alleviate oxidative damage on cell membrane, thus enhancing grape salt tolerance ( Gohari et al, 2021 ).…”
Section: Plant’s Ability To Alleviate Oxidative Stress Is Important F...supporting
confidence: 77%
“…For example, multi-walled carbon nanotubes (MWCNTs), cerium oxide nanoparticles, and zinc oxide nanoparticles (SeNPs and ZnONPs) can significantly alleviate the inhibition of salt stress on the growth of rapeseed seedlings. Seed priming using cerium oxide nanoparticles, SeNPs and ZnONPs, also significantly improves the germination rate of rapeseed seeds under salt stress ( Rossi et al, 2017 ; Zhao et al, 2019 ; El-Badri et al, 2021 ; Khan et al, 2021 ; Li et al, 2022 ). For more details, please refer to Table 1 .…”
Section: Use Of Nanomaterials: An Emerging Approach To Improve Plant ...mentioning
confidence: 99%
See 1 more Smart Citation
“…ROS accumulation is commonly observed during seed imbibition [ 47 ]. Luo et al [ 45 ] demonstrated that salinity-induced ROS accumulation inhibited seed germination.…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) are the key enzymes involved in the metabolism of ROS. An increase in their activities contributes to the removal of ROS [ 47 ].…”
Section: Introductionmentioning
confidence: 99%